Survivor benefits and the gender tax gap in public pension schemes : observations from Germany - Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2005)
Since its inception, the traditional form of providing survivor benefits within public pension schemes has lost much of its legitimacy. As a result of fundamental changes in marriage behaviour and the typical division of labour between married spouses, offering noncontributory benefits of this kind could be seen as inequitable. Since these benefits usually substitute for non-derived pension entitlements based on the surviving spouse's own contributions, they can also lead to incentive effects, especially for married women with some degree of labour-force attachment, that appear to be far from optimal. The present paper highlights this problem referring to institutional details and empirical results related to Germany and shows how it could be resolved by jointly annuitizing a given couple's pension entitlements.
Keywords: J16; J22; H55; 330; public pensions; survivor benefits; female labour supply; optimal taxation; Gesetzliche Rentenversicherung; Rendite; Geschlecht; Frauenerwerbstätigkeit; Sozialversicherungsbeitrag; Optimale Besteuerung; Schätzung; Deutschland